Thixotropy of levator palpebrae as the cause of lagophthalmos after peripheral facial nerve palsy. Issue 5 (1st May 2002) - Aramideh, M; Koelman, J H T M; Devriese, P P; Speelman, J D; Ongerboer de Visser, B W
Abstract : Patients with facial nerve palsy are at risk of developing corneal ulceration because of lagophthalmos (incomplete closure of the affected eyelid). Lagophthalmos could result from thixotropy of the levator palpebrae muscle—that is, the formation of tight crossbridges between the actin and myosin filaments of the muscle fibres causing stiffness of the muscle—rather than from paralysis of the orbicularis occuli muscle as previously supposed. This possibility was investigated in 13 patients with a peripheral facial nerve palsy in a prospective open study. The levator muscle of the affected eyelid was stretched by manipulation and downward movement of the passively closed upper eyelid for ∼15 seconds. The amount of lagophthalmos was measured before and immediately after this manoeuvre. In all patients except one there was a clear reduction in lagophthalmos (mean reduction 72%; range 60–100%). Thus in this setting the lagophthalmos appears to be caused by thixotropy of the levator palpebrae muscle, which has implications for treatment.